The Role of Mediation Electronic Word of Mouth (E-WoM) in Relationship Quality of Services and Tourism Products Against Visiting Decisions - Taryadi, Asep Rahmat; Miftahuddin, Muchammad Agung (Journal of Economics Research and Social Sciences, 2021)
The purpose of this study was to analyze the mediating role of electronic word of mouth in the relationship between tourism products and service quality on the decision to visit tourists to Pangandaran Beach. This research is explanatory research, and the data collection is done by distributing questionnaires. The sample in this study amounted to 95 visitors to Pangandaran beach, who were selected using the purposive sampling method. Based on the analysis using Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach, the results indicate that service quality and tourism products have a significant positive effect on visiting decisions. However, electronic word of mouth does not mediate the relationship between service quality and tourism products on tourists visiting decisions.